Current management strategies and the potential of inhaled GM-CSF for the treatment of autoimmune pulmonary alveolar proteinosis. (4th March 2019) - Piloni, Davide; Campo, Ilaria
ABSTRACT: Introduction : Pulmonary alveolar proteinosis (PAP) is an ultra-rare syndrome the peculiarity of which is the accumulation of surfactant within the alveolar spaces, which can lead to respiratory failure and death. The autoimmune form (approximately 90% of cases) is characterized by the presence of neutralizing autoantibodies anti granulocyte monocyte-colony stimulating factor (GM-CSF), which impair alveolar macrophage functions. Areas covered : This review delineates the standard therapeutic strategy based on whole lung lavage (WLL) and the potentiality of the incoming inhaled treatment for PAP. Expert opinion : WLL is the current gold standard treatment for PAP, however a number of non responders have been reported and the requirement of repeated lavages is not unusual. In addition, WLL is an invasive procedure that has not yet been standardized, which needs to be performed in specialized centers, under general anesthesia in an intensive care unit, even if associated with a low rate of complications. Inhaled GM-CSF is feasible as 'at home' therapy and might be a promising therapeutic option for PAP, nevertheless, definite guidelines for GM-CSF therapy are still lacking and the data supporting GM-CSF supplementation as first line treatment are not conclusive.